Development and validation of the craving automated scale for alcohol - Vollstädt-Klein, Sabine; Kiefer, Falk (Alcoholism, 2015)
Background: Alcohol consumption has been suggested to be associated with a dysregulation in habit formation and execution in dependent patients. Although there are established craving questionnaires assessing various components of craving, to our knowledge, no questionnaire exists to assess habitual and automated substance intake. In this study, we present and validate the “Craving Automated Scale for Alcohol” (CAS-A), a newly developed questionnaire assessing craving and other components of automated addictive behavior. Methods: Forty-three recently detoxified alcohol-dependent patients were examined in an inpatient setting using a cross-sectional design. The CAS-A, a self-report questionnaire, was applied. According to classical test theory, we conducted principal component analyses (PCAs) to identify the components of CAS-A, after which we validated it using established craving questionnaires. Thirty-two healthy participants served as a control group. Results: Our first-order PCA identified a 5-factor solution. A second-order analysis then identified 2 general factors. These factors were partially associated with established craving measures and with the severity of dependence. Conclusions: Our findings suggest that CAS-A assesses additional components of addictive behavior compared to established measures. We interpret the 5 CAS-A factors as “only aware in hindsight,” “no deliberate decision,” “contrary to intention,” “no perception,” and “no control.” We suggest the 2 general factors be interpreted as “unaware” and “nonvolitional.” Our results indicate that the CAS-A indeed assesses some components of automated craving and automated drinking behavior in a more sophisticated way than established questionnaires. The CAS-A as a retrospective questionnaire can be considered to be a trait rather than a state measure.